PENGARUH PENERAPAN GOOD CORPORATE GOVERNANCE TERHADAP KINERJA KEUANGAN PERUSAHAAN - Susanti, Eni; Sudantoko, Djoko (PRESTASI, 2012)
Recent developments have proven that the companys management is not enough just to make sure if the management arrangements work well and efficiently, corporate governance is corporate governance to explain the relationship between the various participants in the company which determines the direction of the companys performance. Performance of the company itself can be seen through the companys financial performance can be measured using the Net Profit Margin, Return on Assets, Return on Equity, Earnings per Share, and Tobins Q. Net Profit Margin, Return on Assets, Return on Equity and Earnings per Share is itself a companys profitability level analysis tool that uses the concept of conventional income. Tobins Q is the ratio of which is a concept that shows the current estimate of the financial markets about the value of the return on investment. If the q-ratio above one, indicating that investment in income producing assets that provide higher value than investment spending, this will stimulate investment. The purpose of this study was to determine the effect of direct application of good corporate governance as measured by a score of Corporate Governance Perception Index of the companys financial performance.Sample of this research is that companies follow the assessment of the implementation of Good Corporate Governance and entered the top 10 Corporate Governance Perception Index by the Indonesian Institute for Corporate Governance. The number of samples in this study was 45 from 2006-2010. Analytical techniques used to test the hypothesis is a simple linear regression analysis to determine the effect of the implementation of Good Corporate Governance for the companys financial performance.From the research that has been done obtained results that the application of good corporate governance has a positive effect on a companys financial performance as measured by the Net Profit Margin, Return on Assets, Return on Equity, Earnings per Share, and Tobins Q.Keywords: Good Corporate Governance, Net Profit Margin, Return on Assets, Return on Equity, Earning per Share, Tobinâs Q